2013
DOI: 10.1039/c3lc50849h
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheted electrophoresis for rapid particle transport

Abstract: Ratcheted electrophoresis of contact-charged particles allows for high speed transport through microfluidic channels over large distances and even against fluid flows. Using a set of predictive design heuristics, we demonstrate an extension of this microfluidic ratchet to separate conductive particles from a particle suspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 30 publications
1
63
0
Order By: Relevance
“…A ratchet is a non-equilibrium scheme that rectifies the motion of randomly moving particles without a net applied force in the direction of transport, by breaking symmetries of the particle motion in space and time. Ratcheting is the operative mechanism of biological enzymes, pumps, and motors [1,2], and has been experimentally realized in particle separators and sorters [3][4][5][6][7][8]. In particular, a "flashing" ratchet works by switching, continuously or instantaneously, between two states of the potential surface on which the particle travels ( Figure 1a): (i) a surface with periodic features that are asymmetric in the direction of transport, and (ii) a surface that allows random, isotropic diffusion of a particle (i.e., a flat potential).…”
Section: Introductionmentioning
confidence: 99%
“…A ratchet is a non-equilibrium scheme that rectifies the motion of randomly moving particles without a net applied force in the direction of transport, by breaking symmetries of the particle motion in space and time. Ratcheting is the operative mechanism of biological enzymes, pumps, and motors [1,2], and has been experimentally realized in particle separators and sorters [3][4][5][6][7][8]. In particular, a "flashing" ratchet works by switching, continuously or instantaneously, between two states of the potential surface on which the particle travels ( Figure 1a): (i) a surface with periodic features that are asymmetric in the direction of transport, and (ii) a surface that allows random, isotropic diffusion of a particle (i.e., a flat potential).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Yao demonstrated non-contact electrostatic charging of droplets by polarizing a neutral droplet and splitting it into two oppositely charged daughter droplets in a T-junction microchannel [86]. Recently, Bishop et al reported a series of works for contact charge electrophoresis (CCEP) of particles [20,75,106,107]. They focused on the rapid transport of particles or mixing by particle motion in microchannels.…”
Section: Fundamentals and Applicationsmentioning
confidence: 97%
“…Modeling of drop/particle motion experiencing the contact charging phenomenon is one of the key subjects in this field [4][5][6]66,[74][75][76][77][78][79][80][81][82]. In microfluidics field, the direct contact charging is used to manipulate droplet [38,[83][84][85][86] or particle motions [20,75] in microchannels in addition to digital microfluidic approaches [6,23,70,77,[87][88][89]. The details of each category will be covered in the following fundamentals and applications section.…”
Section: Historymentioning
confidence: 99%
“…Drews et al demonstrated that this oscillatory motion can be rectified to obtain directed transport of micron sized particles in a microfluidic channel. 7 In order to achieve this, they fabricated a microfluidic channel containing inclined PDMS barriers at alternative positions and flanked by gallium electrodes (Fig.2b). In a medium of a dielectric liquid (mineral oil), they suspended the conductive micro-particles (silver electrodes, the particles acquire a net charge corresponding to the charge of the electrode and begin to translate in the opposite direction.…”
Section: Particle Transport In Ratcheted Systemsmentioning
confidence: 99%